Formation of the CuII–Phenoxyl Radical by Reaction of O2 with a CuII–Phenolate Complex via the CuI–Phenoxyl Radical. Issue 69 (7th November 2019) - Suzuki, Takashi; Oshita, Hiromi; Yajima, Tatsuo; Tani, Fumito; Abe, Hitoshi; Shimazaki, Yuichi
Abstract: Reaction of Cu(ClO4 )2 ⋅ 6 H2 O with a tripodal 2N2O ligand, H2 Me2 NL, having a p ‐(dimethylamino)phenol moiety, in CH2 Cl2 /MeOH (1:1 v/v) under basic conditions under an inert gas atmosphere gave [Cu(Me2 NL)(H2 O)] (1 ). The same reaction carried out under aerobic conditions gave [Cu(Me2 NL)(MeOH)]ClO4 (2 ), which could be obtained also from the isolated complex 1 by reaction with O2 in CH2 Cl2 /MeOH. The X‐ray crystal structures of 1 and 2 revealed similar square‐pyramidal structures, but 2 showed the (dimethylamino)phenoxyl radical features. Complex 1 exhibits characteristic Cu II EPR signals of the d x 2 - y 2 ground state in CH2 Cl2 /MeOH at 77 K, whereas 2 is EPR‐silent. The EPR and X‐ray absorption fine structure (XAFS) results suggest that 2 is assigned to the Cu II –(dimethylamino)phenoxyl radical. However, complex 1 showed different features in the absence of MeOH. The EPR spectrum of the CH2 Cl2 solution of 1 exhibits distortion from the d x 2 - y 2 ground state and a temperature‐dependent equilibrium between the Cu II –(dimethylamino)phenolate and the Cu I –(dimethylamino)phenoxyl radical. From these results, Cu II –phenoxyl radical complex 2 is concluded to be formed by the reaction of 1 with O2 via the Cu I –phenoxyl radical species. Abstract : Copper radicals : The reaction of the Cu II –phenolate complex with O2 forms the Cu II –phenoxyl radical complex (see scheme). The Cu II –phenolate complex is in a temperature‐dependent equilibrium between the Cu II –phenolate and Cu I –phenoxyl radical complexes. These results suggest that a Cu II –phenoxyl radical complex was formed via the Cu I –phenoxyl radical intermediate.